Screening of Streptomyces spp. Isolated from a Cameroonian Ecosystem for Biological Control of Cassava Bacterial Blight Disease - Nardis, Nkoudou Ze; Loïc, Ze Abada; Olivier, Bébiné Biédi Didier; Ngang, Jean Justin Essia (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2026)
The global increase in cassava bacterial blight disease (CBB) caused by Xanthomonas axonopodis pv. manihotis (Xam) has been leading to the investigation of new strategies to tackle this problem. This study aimed to evaluate the antibacterial potential of 30 soil Streptomyces strains by initial screening against Xam, isolated from infected cassava leaves. The isolates demonstrating the strongest inhibitory effects were selected to extract their methanolic secondary metabolites following practical antibacterial biocontrol assessment. This was done by treating infected cassava plants with the methanolic extracts and monitoring for 14 days. The results showed that, among the 30 soil streptomyces strains, two isolates, encoded BEL_12 and KER_2, exhibited strong inhibitory effects. Their methanolic extracts showed inhibitory activity against Xam, with minimum inhibitory concentration (MIC) values of 32 µg/ml for BEL_12 and 2 µg/ml for KER_2. The CBB incidence on cassava leaves KER_2 and BEL_12 methanolic extracts was 24% and 88%, respectively. This study demonstrated the remarkable potential of Cameroonian soil Streptomyces spp. to produce bioactive compounds that suppress CBB and lay the basis for developing sustainable, eco-friendly biocontrol agents to reduce reliance on chemical pesticides in affected regions.